Aplikasi Teknologi Mesin Pembuatan Tusuk Bakso Ayam Bakar di Desa Karang Anyar, Lampung Timur - Isnaini Rahmadi; Madi Madi; Syahrizal Nasution; Dina Fithriyani (Jurnal Pengabdian Pada Masyarakat, 2021)
APPLICATION OF MACHINE TECHNOLOGY FOR MAKING GRILLED CHICKEN MEATBALSS IN KARANG ANYAR VILLAGE, EAST LAMPUNG. The business of craftsmen for grilled chicken meatball sticks from bamboo continues to grow along with the number of meatballs stick sellers in Karang Anyar Village, East Lampung. However, the tools used to produce grilled chicken meatball skewers are still very simple and require a long time to produce grilled chicken meatball skewers with good quantity and quality. Therefore, the service team provides a solution for the application of machine technology for making grilled chicken meatball skewers that are more modern and able to increase the quantity of grilled chicken meatball skewers in a faster time. The solution offered is in the form of new technology with a mechanical pattern system that saves more energy, costs and production time. The program stages begin with service planning, implementation of service by assembling tools, applying tools to the target community, analyzing results, and evaluating the program. The results obtained from this program are the 3 in 1 grilled chicken meatball skewer which is implemented by the people of Karang Anyar Village, East Lampung, thereby increasing the quality and quantity of the grilled chicken meatball sticks produced. This program was also published on two social media. It is hoped that in the future this program can continue to apply the technology of grilled chicken meatball skewers in various potential communities.